(3GdNSGQI (B:s (3eaghegG h eYGjjQ GMJSGHgG h JWHjbGJgG aj Gdabg GdGSdGej (B/s - (3Hf eMeO, GMeO GMeO cdjHs ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2010)
(3eaghe GdNSGQI h CfhGYgG h GdCdaGX PGJ GdUdI , GdhSGFd GdTQYjI deYGdLI GdNSGQI bHd h HYO hbhYgG , CSHGH GdNSGQI h WQb JfajPgG , eYGjjQ MSGH GdNSGQI , JWHjbGJ GdNSGQI YfO GdabgGA h CSGdjH ehGLgJgG aj GdeUGQa GdGSdGejI (B.s
(3eQGLY U(B.403s
Keywords: (3GdEbJUGO GdESdGejs; (3GdHfhc GdGSdGejIs; (3GdNSGFQ GdeGdjIs